Implementasi Labview Untuk Pemantauan Pemakaian Energi Listrik - Muhammad Yusuf Yunus; Marhatang Marhatang (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
In conventional electric measurement devices, measurements are made on the use of electrical energy as a whole where consumers can only see information on the results of the use of electrical energy by looking at the total power consumption amount indicated on the meter kWh meter. Based on the above problems, the author aims to raise the title "Design of Monitoring System of Electricity Energy Usage using LabVIEW". The LabVIEW program has the ability to measure, monitor and store data quickly and accurately. With this tool will be realized a design system monitoring the use of electrical energy in real time through the computer instead of kWH meter analog or digital. This concept is one of the energy management solutions that enable consumers to obtain statistical data on electrical energy consumption in detail. From the results of monitoring the use of loads, obtained very good results in monitoring the usage of energy, which in this case using household burden.